ETHICAL AND JURIDICAL DILEMMAS IN THE PROSECUTION OF MURDERERS WITH MENTAL DISORDERS: PERSPECTIVES OF ISLAMIC LAW AND INDONESIAN POSITIVE LAW - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to analyse the ethical and juridical dilemmas in the prosecution of mentally ill murderers from the perspective of Islamic Law and Indonesian Positive Law. The ethical debate arises from the need to balance the principles of justice for the victim and compassion for the mentally ill offender. In Islamic Law, mentally ill perpetrators are generally not held fully responsible for their actions and may be granted a reduced or commuted sentence. In contrast, in Indonesian Positive Law, mentally disordered offenders can be exempted from criminal responsibility under Article 44 of Law No. 8 of 1981 on Criminal Procedure, although it is still possible to subject them to other measures such as psychiatric treatment. This study underscores the importance of medical and humanitarian assessments in the prosecution process, as well as the need for a balance between justice for victims and protection of the human rights of mentally ill offenders.